On \(I\)-Lacunary Double Statistical Convergence of Weight \(g\) - Savas, Ekrem (Communications in Mathematics and Applications, 2017)
In this paper, our aim is to introduce new notions, namely, \(I\)-statistical double convergence of weight \(g\) and \(I\)-lacunary double statistical convergence of weight \(g\). We mainly investigate their relationship and also make some observations about these classes.